RiskBenefit4EU – Partnering to strengthen the risk-benefit assessment within EU using a holistic approach - Assunção, Ricardo (2018)
“RiskBenefit4EU – Partnering to strengthen the risk-benefit assessment within EU using a holistic approach” is a recent European pilot project funded by EFSA and coordinated by Portugal (PT). This project integrates a multidisciplinary team from health and food institutes, national food safety authorities, R&D institutions and academia from PT, Denmark (DK) and France (FR). The main objectives of RiskBenefit4EU concerns the development of a set of RBA tools that can estimate the overall health effects of foods, food ingredients and diets and that can be applied to data from different countries. RiskBenefit4EU aims to strengthen the EU capacity to assess and integrate food risks and benefits using an holistic approach integrating the areas of toxicological, nutritional and microbiological components through the development of a harmonized framework. This pilot project will validate the RBA framework created using data from different areas of the Portuguese reality: a Portuguese case study on breakfast cereals, including results obtained under the MYCOMIX project (https://www.youtube.com/watch?v=CsKaz3mt2J4), the National Food, Nutrition, and Physical Activity Survey (IAN-IF, https://ian-af.up.pt/) and data provided under the National Sampling Plan (PNCA, http://www.asae.gov.pt/).